Cash, non-cash, or mix? Gender matters! The impact of monetary, non-monetary, and mixed incentives on performance - Hanna M. Sittenthaler; Alwine Mohnen (Journal of Business Economics, 2020)
Standard economic theory asserts that cash incentives are always better than non-cash ones, or at least not worse. This study employs a real effort experiment to analyze the impact of monetary, non-monetary, and a combination of monetary and non-monetary incentives on performance, where non-monetary incentives are defined as tangible incentives with market value. Our overall results suggest that there exists no significant difference in performance in response to monetary, non-monetary, and mixed incentives. However, gender-based differentiation reveals a different picture: the performances of men and women depend upon the type of incentive used. Whereas men's performance is significantly higher in response to monetary incentives compared to non-monetary ones, women's performance is significantly higher in response to non-monetary incentives. The gender differences in the effectiveness of monetary and non-monetary incentives do not seem to be triggered by the perceived attractiveness of the non-monetary incentives but rather by the differences between men and women in the feelings of appreciation and perceived performance pressure in a tournament setting. Therefore, our results indicate that gender differences must be considered when implementing incentives.
Keywords: C91; D01; J16; J33; M52; 650; Monetary incentives; Non-monetary incentives; Mixed incentives; Gender differences; Work performance; Experiment